Demand shifts and imperfect competition. - Cowan, S (Department of Economics (University of Oxford), 2004)
The effects of demand shifts on output, price and profits in imperfectly competitive industries with no entry or exit are derived. Four types of demand shift are modelled: additive and multiplicative shifts of the demand and inverse demand functions. Necessary and sufficient conditions for output, price and profits to increase with an outward demand shift are derived for each case. Either output or the price, but not both, may fall with a positive demand shift. Profits may also fall for a Cournot oligopoly. Log-concavity of the direct demand function is sufficient for the standard results to go through.